Understanding Financial Literacy and Competence: Considerations for Training, Collaboration, and Referral for MFTs - Bryce L. Jorgensen; Damon L. Rappleyea; Alan C. Taylor (Journal of Financial Therapy, 2014)
Developing clinical competencies is a foundational feature for most mental health disciplines. Evidence suggests that many couples attending marital therapy regularly report that financial concerns are a significant contributor to their collective distress. Despite the reports of financial distress being a common occurrence, many practitioners are unfamiliar with available resources to remediate the problem. The authors address the concepts of practitioner competence in financial literacy, client financial problems, the benefits of financial literacy, and suggest a referral process, grounded in ethical decision making, that provides appropriate treatment considerations to clients experiencing such distress. The Referral for Financial Concerns Questionnaire (RFCQ) and the Personal & Relationship Financial Assessment Tool (PREFAT) are introduced. Finally, the authors provide suggestions for professional collaboration between mental health practitioners, financial planners, and financial counselors.
Keywords: financial competence; couples therapy; financial literacy; MFT training